Bone Surface Micro‐Topography at Craniofacial Entheses: Insights on Osteogenic Adaptation at Muscle Insertions. Issue 12 (13th July 2019) - Walters, Mark; Crew, Michael; Fyfe, Georgina
ABSTRACT: Macroscopic details of the bone–muscle interface are represented by a mosaic of calcified features inclusive of fossae, tuberosities, crests, and ridges. These features are in part of an adaptive osteogenic response to dissipate forces of localized mechanical loading. In an osteoarchaeological or paleontological context, these features are interpreted as "musculoskeletal stress markers" to infer habitual behaviors. Microscopic surveys of bone surface topography of the enthesis can reveal localized osteogenic topologies. These features illustrate the developmental mechanisms that produce these bony forms and contribute to an evidential basis to read these structures. Microscopic osteogenic topographies at sites of gnathic muscle attachments located in the craniofacial skeleton were explored in reference to extrapolated loading vectors in an ontogenetic series of craniofacial skeletons of the primate ( Procolobus verus ). Epoxy resin replicas of bone surfaces were made, and micro‐topographical detail viewed with Scanning Electron Microscope. Osteoclastic bone remodeling was found at entheses associated with presumptive net tensile loading. Mineralized fibrocartilage was present at entheses, associated with presumptive net compressive loading. Collectively, these outcomes suggest that entheses develop through adaptive osteogenic activity in response to differential vectors of local mechanical loading. However, the presence of mineralized fibrocartilage also suggests that proliferative cartilage has a role in the development of bone eminences providing functional processes. This study concludes that the vector of muscle loading at entheses as well as proliferative fibrocartilage is influencing the form of bony eminences in the primate craniofacial skeleton defining functional and species defining morphologies. Anat Rec, 302:2140–2155, 2019. © 2019 American Association for Anatomy